Cytotoxicity of ketamine, xylazine and Hellabrunn mixture in liver-, heart- and kidney-derived cells from fallow deer - Kovacova, Veronika; Abdelsalam, Ehdaa Eltayeb Eltigani; Bandouchova, Hana; Brichta, Jiri; Havelkova, Barbora; Piacek, Vladimir; Vitula, Frantisek; Pikula, Jiri (Neuro endocrinology letters, 2016)
OBJECTIVES: Chemical restraint of wild animals is practiced to accomplish intended procedures such as capture, clinical examination, collection of diagnostic samples, treatment and/or transport. Extra-label use of animal medicinal drugs is often necessary in wildlife because most approved therapeutics do not list wild species on the labelling. Here, we used cellular in vitro models, a cutting-edge tool of biomedical research, to examine cytotoxicity of anaesthetic agents in fallow deer and extrapolate these data for anaesthetic risks in wildlife. METHODS: We examined the cytotoxic effects of ketamine, xylazine, and ketamine-xylazine, i.e. the Hellabrunn mixture, on liver-, heart- and kidney-derived cell cultures prepared from a fallow deer (Dama dama) specimen. In line with preliminary studies we exposed cells to 10 µM, 50 µM, 100 µM, 1 mM, and 10 mM ketamine or xylazine. The combination of ketamine-xylazine was dosed at 0.025+0.02 mg/ml, 0.05+0.04 mg/ml, 0.75+0.06 mg/ml, 0.1+0.08 mg/ml, and 0.125+0.1 mg/ml per one well containing 10 000 cells. The quantification of cytotoxicity was based on lactate dehydrogenase activity released from damaged cells. RESULTS: Liver-derived cells show higher sensitivity to the cytotoxic effects of both ketamine and xylazine administered as single drugs when compared with cells cultured from the heart and kidney. The Hellabrunn mixture induced significantly higher cytotoxicity for kidney-derived cells ranging from 16.78% to 35.6%. Single and combined exposures to ketamine and xylazine resulted only in high-dose cytotoxicity in the heart-derived cells. CONCLUSIONS: Our results indicate that immobilization drugs significantly differ in their cytotoxic effects on cells derived from various organs of the fallow deer.
Keywords: Liver; Xylazine; ketamin; játra; testy toxicity; xylazin; Analgesics; Cytotoxins; vysoká zvěř; zvířata; analgetika; ledviny; Deer; Heart; Kidney; Ketamine; cytotoxiny; Toxicity Tests; srdce; Animals